A Neural Network Model for Social-Aware Recommendation - Xiao, Lin; Min, Zhang; Yiqun, Liu; Shaoping, Ma (Information Retrieval Technology, 2017)
Social-aware recommender systems have been popular with the rapid growth of social media applications. Existing approaches have attempted to accommodate social information into typical Collaborative Filtering methods and achieved significant improvements. Neural networks are gaining increasing interests in information retrieval tasks. However few studies have considered applying neural network in social-aware recommendation tasks. In this paper, we aim to fill this gap and propose a social-aware neural recommender system. Extensive experiments on real-world datasets demonstrate that our model outperforms state-of-art approaches significantly.